Livestock and food security in Ethiopia: An overview - Mussa, M. (Agricultural Economics Society of Ethiopia, 1995)
Addresses the contribution of livestock to food security in Ethiopia and to make suggestions on how to eliminate or alleviate the constraints facing the subsector for increased and sustainable contribution to food security. Presents data on the total and per capita production and yield of Meat, consumption of Meat, consumption of total milk in selected sub-Sahara African countries and beef consumption in Addis Ababa by Income categories, 1994, projected beef consumption in Addis Ababa, 1995-2010. Discusses the contribution of livestock directly and indirectly to food security. The direct contribution includes meat and milk whereas the indirect contributions include draft power, manure and income from sales & livestock and livestock products which are often used for the purchase of food grain during bad harvests.